(untitled) (CAHIERS MAGELLANES-NS, 2024)
Each community celebrates festivals to express its uniqueness widely throughout the world; and they reflect their own tradition. Celebrating festivals among children and adults, it brings joy and refreshment with them. In India festivals are associated with culture; it includes dressing, eating, grouping with relatives, gaming between people, farming and educating the youngsters. This article examines some of the crucial festivals celebrated in India.